Pseudotumor Cerebri Without Edema - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The pathologic findings in two adult patients with idiopathic intracranial hypertension (IIH) who died unexpectedly are reported from the University of Iowa College of Medicine, Iowa City.